2000
DOI: 10.1046/j.1365-2958.2000.01719.x
|View full text |Cite
|
Sign up to set email alerts
|

The Tat protein export pathway

Abstract: SummaryThe Tat ( twin-arginine translocation) system is a bacterial protein export pathway with the remarkable ability to transport folded proteins across the cytoplasmic membrane. Preproteins are directed to the Tat pathway by signal peptides that bear a characteristic sequence motif, which includes consecutive arginine residues. Here, we review recent progress on the characterization of the Tat system and critically discuss the structure and operation of this major new bacterial protein export pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
497
0
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 544 publications
(512 citation statements)
references
References 99 publications
13
497
0
2
Order By: Relevance
“…This is true of protein translocation whether the protein is in the unfolded state, as in sec-dependent protein translocation, or in the folded state, as occurs in the export of metalloproteins through the Tat pathway of bacteria [1][2][3] . Bacterial toxins such as anthrax are also examples of proteins that translocate across membranes but here a much scaled-down apparatus is employed involving pore-forming subunits 4 .…”
Section: Discussionmentioning
confidence: 99%
“…This is true of protein translocation whether the protein is in the unfolded state, as in sec-dependent protein translocation, or in the folded state, as occurs in the export of metalloproteins through the Tat pathway of bacteria [1][2][3] . Bacterial toxins such as anthrax are also examples of proteins that translocate across membranes but here a much scaled-down apparatus is employed involving pore-forming subunits 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Proteins recognized by the Tat translocation pathway contain a double arginine at their extreme N-termini. These proteins are translocated in a folded state (Berks et al, 2000). It is believed that halobacterial proteins already have to fold in the cytoplasm to circumvent precipitation caused by the high internal salt concentration.…”
Section: Signal Peptidesmentioning
confidence: 99%
“…Nonetheless, it has been known that Yid pathway is involved in the threading mechanism for unfolded proteins only. Furthermore, it was previously unknown whether there existed another folded protein export pathway, in addition to the Tat pathway, that was large enough to allow translocation of the folded protein (Berks et al, 2000). Thus, we concluded that the Yid translocon has a much smaller diameter for transporting the folded GFP with an anchor function and a neutral N-terminal sequence compared with the Sec translocon, showing both blocked and low levels of GFP expression of those with an anchor function sequence and an alkaline N-terminus (Fig.…”
Section: Effect Of N-terminal Pi With An Anchor Function On Gfp Exprementioning
confidence: 99%